Accordance of Schools Health Status with the Regulations of School Health in Yazd - Mahmoud Zare Jamalabadi; Mohammad Bagher Kajbaf; Ehsan Mohiti Ardakani (Shahid Sadoughi University of Medical Sciences, 2014)
Introduction: A large body of literature on school health and review of its history in the world show that most of the countries have paid special attention to this issue. The student's health is of high importance, not only for being the society vulnerable population, but for they are future national and human capital and guarantors of the country socioeconomic development. Materials and Methods: In this descriptive study the statistical population included all 110 primary schools (girls' and boys') in Yazd, District 2 of which 50 were randomly selected. Data were gathered using a questionnaire with two separate parts; the first part about environmental health and safety status of the schools and the second about their public health status. The questionnaire validity was confirmed by the experts' judgment and reliability was estimated 82% using Cronbach's alpha test. Results: Most of the schools had suitable area per student, health care rooms, standard first aid kit, appropriate drinking fountains, and standard toilets. In 66% of the schools the distance of the blackboard from the first student was ≥2.5 m. Most of the schools had appropriate indexes for the status of light, ceiling, color and class wall. Conclusion: The results of this study indicated that the health status of primary schools of Yazd, District 2 was consistent with the required standards of school health regulations. Health status was not significantly different in girls' and boy's schools.